An Efficient Biomimetic Aerobic Oxidation of Alcohols Catalyzed by Iron Combined with Amino Acids - Zhang, Guofu; Li, Shasha; Lei, Jie; Zhang, Guihua; Xie, Xiaoqiang; Ding, Chengrong; Liu, Renhua (Synlett, 2016)
A novel combination of FeCl3, l-valine and TEMPO is found to oxidize alcohols to the carbonyl compounds with dioxygen. A wide range of primary/secondary benzyl, allylic, and heterocyclic alcohols have been efficiently converted into aldehydes and ketones with good to excellent isolated yields.
Keywords: alcohols; aldehydes; amino acids; iron; ketones; oxidation